Roof collapse accumulation and stress evolution characteristics of double-inclined mining in steeply inclined medium-thick coal seam - WU Yongping; XU Yingrui; XIE Panshi; WANG Hongwei; LANG Ding; HUANGFU Jingyu; QIANG Xubo; DU Yuqian; WANG Lechen; RU Xiaohui; WANG Zhengfu (Gong-kuang zidonghua)
The pseudo-inclined mining has limited capacity to reduce the inclination angle of working face, necessitating breakthroughs in longwall comprehensive mechanized mining methods for steeply inclined medium-thick coal seam with inclination angles exceeding 60°. Taking the 3212 working face in the Lüshuidong Coal Mine of Huayingshan Coal Industry Co., Ltd. as the engineering background, a double-inclined mining method was proposed based on pseudo-inclined mining. Physical similarity simulation and numerical simulation were employed to analyze the movement and accumulation patterns and stress evolution of the gangue filling after roof breaking in double-inclined mining. The results showed that the layout of the double-inclined working face needed to be coordinated with the mine’s mining design, and the maintenance of two roadways of the working face was challenging. The return air roadway side was significantly affected by the mining stress, while coordinating the transportation roadway with the working face support was also difficult. Due to the irregularly shaped goaf roof structure, the double-inclined mining had larger collapse steps, and its gangue collapse accumulation formed an inverted triangular pattern with periodic sliding characteristics. The accumulation of large gangue blocks resulted in non-uniform pressure in the upper and middle sections of the working face. In double-inclined mining, the original rock stress increased gradually with the advancing distances of the working face, with varying pressure intensities in the upper, middle, and lower inclined sections of the working face. Generally, the upper and middle sections experienced greater pressure than the lower section, but the stress concentration factor of the support pressure was higher in the lower inclined section compared to that in the upper and middle sections of the working face. The stress evolution characteristics of the roof in double-inclined mining were influenced by the working face shape and advancing distance. Additionally, the roadway inclination angle adjustment caused the range of stress release to decrease asymmetrically from the upper to the lower inclined sections.